Privatization as a Valid Alternative - Millett, Sawin (Maine Policy Review, 1993)
At the "Rethinking State Government" conference held at the University of Maine in January 1993, a panel explored the issue of privatization, of using private enterprise to provide public sector services. Sawin Millet provides the perspective of someone who has worked primarily in the public sector.